Peningkatan Keterampilan Berbicara Siswa Menggunakan Model Role Playing Pada Pembelajaran Wawawancara - Indra Rendyana; Dudung Suryana; Riga Zahara Nurani (Universitas Muhammadiyah Kuningan, 2025)
This study aims to improve students' speaking skills through the application of role playing model in interview learning in class IV SDN Budiwangi. This research used the Classroom Action Research (PTK) method which was carried out in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data were obtained through observation, documentation, and performance tests. The results showed that lesson planning had been carried out very well, indicated by the average planning score of 4.00 in cycles I and II. Learning implementation showed an increase from cycle I with an average score of 3.60 to 4.00 in cycle II, with a percentage increase of 11.11%. In addition, student learning outcomes in speaking skills also experienced a significant increase. In cycle I, the average performance test score was 74.16 with 66.7% completeness, increasing in cycle II to 85.33 with 86.66% completeness. The percentage increase in learning outcomes reached 15.06%. The conclusion of this study is that the role playing model is effective in improving students' speaking skills in interview learning. Therefore, it is suggested that teachers can utilize this model as an alternative to interesting and participatory learning strategies, especially for materials that demand students' communication skills.